Efeito da administração crônica de eritropoietina e treinamento físico sobre a modulação autonômica cardiovascular em ratos wistar - SANTOS, Milena Samora dos (2016)
Erythropoietin (EPO) is a glycoprotein hormone produced primarily by the kidney when there is a decrease in circulating oxygen level and your main function is to regulate erythropoiesis. Analog of EPO invaded the backstage of sporting high performance scenario, especially in aerobic modalities, because it acts on the heart, circulation, aerobic endurance, leading to an increased tissue oxygenation, decreasing the feeling of fatigue and an ergogenic function. Furthermore, it is known that EPO has actions in non-hematopoietic tissues with anti-apoptotic function, anti-inflammatory, cell proliferation and differentiation. Thus, this study aimed to evaluate the effects of chronic administration of EPO combined with exercise training on cardiovascular autonomic modulation in rats. For this, the animals were divided into four groups: sedentary control group (SCG, n = 10), trained control group (TCG, n = 8), sedentary EPO group (SEG, n = 10) and trained EPO group (TEG, n = 8). 50 IU / kg EPO were administered (subcutaneously) and swimming training (increasing volume and intensity). After eight weeks of protocol we evaluated the baseline heart rate (HR) and blood pressure (BP), baroreflex sensitivity, cardiac autonomic tone, HR variability (HRV), systolic BP (SBPV) and diastolic (DBPV), cardiac hypertrophy and cardiac and renal fibrosis. For all the results we used a significance level of p≤0,05. The animals of the SEG and TEG showed increased levels of red blood cells, hemoglobin and hematocrit, compared with their respective control groups. The animals of the TCG exhibited rest bradycardia compared to SCG and an increased in value of the spectral high frequency (HF) in HRV. However, the EPO has triggered an increase in SBP in the sedentary group compared with the SCG, which was not observed in DBP and mean BP (MBP). Also there were no differences in baroreflex sensitivity and VPAS among the groups, only in VPAD where the TEG showed lower value of the spectral component of low frequency (LF) compared to TCG. There was no difference between vagal and sympathetic effect between groups, on the other hand, the TCG showed less sympathetic tone than the SCG. Interestingly, the TEG had higher vagal tone compared with the TCG; the intrinsic rate of heart pacemakers (IRHP) are increased in SEG compared to the SCG; and sympathovagal index was reduced in the group receiving EPO compared to their respective controls. The TCG showed cardiac hypertrophy and SEG presented an increase in diameter of cardiomyocytes as compared to the SCG. Both groups receiving EPO had fibrosis on heart and kidney, compared with control groups. So, our results suggest that the chronic administration of EPO can provide cardiovascular autonomic changes in Wistar rats, like the increase in parasympathetic activity, in an attempt to reverse the increase in IRHP caused by the fibrosis. Our data also indicate that exercise training by swimming was ineffective in reversing the damage observed when using EPO.